Single motor unit activity in human extraocular muscles during the vestibulo-ocular reflex - Weber, Konrad P (Blackwell Science Inc, 2012)
Motor unit activity in human eye muscles during the vestibulo-ocular reflex (VOR) is not well understood, since the associated head and eye movements normally preclude single unit recordings. Therefore we recorded single motor unit activity following bursts of skull vibration and sound, two vestibular otolith stimuli that elicit only small head and eye movements. Inferior oblique (IO) and inferior rectus (IR) muscle activity was measured in healthy humans with concentric needle electrodes. Vibration elicited highly synchronous, short-latency bursts of motor unit activity in the IO (latency: 10.5 ms) and IR (14.5 ms) muscles. The activation patterns of the two muscles were similar, but reciprocal, with delayed activation of the IR muscle. Sound produced short-latency excitation of the IO muscle (13.3 ms) in the eye contralateral to the stimulus. Simultaneous needle and surface recordings identified the IO as the muscle of origin of the vestibular evoked myogenic potential (oVEMP) thus validating the physiological basis of this recently developed clinical test of otolith function. Single extraocular motor unit recordings provide a window into neural activity in humans that can normally only be examined using animal models and help identify the pathways of the translational VOR from otoliths to individual eye muscles.